Developing Learner Autonomy in English as a Foreign Language Classes: Teachers’ Perceptions on Its Feasibility - Silih Warni; Nurhandayani Supraptiningsih; Roslaini Roslaini (UICELL, 2019)
This study examined English as a Foreign Language (EFL) teachers’ perceptions toward how feasible it is to develop learner autonomy in secondary school context in Jakarta. 106 EFL teachers teaching in senior high schools in Jakarta took part and responded questionnaires concerning feasibility for developing learner autonomy in EFL context. The first part of the questionnaire explored the teachers’ perceptions on the feasibility of involving learners in a range of language course decisions associated with learner autonomy. In this regard, teachers perceived that it is most feasible for students to get involved in decision making related to tasks and activities, topics, materials, and classroom management. The least feasible areas of choice are those related to teaching methodology and objectives. The second part of the questionnaire revealed how feasible it was, according to the teachers, for their students to develop a range of abilities associated with the capacity of learner autonomy. The discussion of the findings suggests that teachers’ professional development program needs to take into account the teachers’ understandings of the learner autonomy and the pedagogical aspects concerning how to promote this capacity on students.